Integrating Network Pharmacology and Experimental Validation to Investigate the Mechanism of Qushi Huatan Decoction Against Coronary Heart Disease - Yin C; Lan T; Wu Y; Cai J; Li H; Kuang X; Jiao L; Ou X; Yang H; Liu B; Lu W (Dove Medical Press, 2024)
Chunxia Yin,1,* Taohua Lan,2,3,* Yunshan Wu,4,5 Jing Cai,1 Haoxiang Li,1 Xiaolan Kuang,1 Lin Jiao,1 Xiaomin Ou,1 Hua Yang,2 Bo Liu,3- 5 Weihui Lu2,6,7 1The Second Clinical Medical College, Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 2Department of Cardiology, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, People's Republic of China; 3State Key Laboratory of Dampness Syndrome of Chinese Medicine, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 4Guangzhou Key Laboratory of Chirality Research on Active Components of Traditional Chinese Medicine, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, People's Republic of China; 5Guangdong Provincial Key Laboratory of Clinical Research on Traditional Chinese Medicine Syndrome, Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 6State Key Laboratory of Traditional Chinese Medicine Syndrome, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 7Chinese Medicine Guangdong Laboratory, Guangdong Hengqin, People's Republic of China*These authors contributed equally to this workCorrespondence: Weihui Lu, Bo Liu, The Second Clinical Medical College, Guangzhou University of Chinese Medicine, Email weihui.lu@gzucm.edu.cn; doctliu@gzucm.edu.cnPurpose: This study was designed to evaluate the effect and mechanism of the Qushi Huatan (QSHT) decoction against coronary heart disease (CHD) through network pharmacology and experimental verification.Methods: In the present study, the active ingredients of the QSHT decoction were identified by ultra performance liquid chromatography/tandem mass spectrometry (UPLC/MS), then the potential ingredients and coronary heart disease targets were predicted using the SwissTarget Prediction database and the database of Genecards and OMIM database, respectively. A herb-compound-target network was constructed using Cytoscape. GO and KEGG enrichment analysis were performed using the ClusterProfiler data package of R software. Molecular docking was used to predict the core targets of QSHT against CHD. In addition, we used a myocardial infarction (MI) and high-fat diet ApoE−/− mice model to investigate the cardioprotective effects of QSHT. Western blotting and immunochemistry were used to verify the core targets and the signaling pathway.Results: A total of 68 active ingredients were found in the QSHT decoction. Network pharmacology indicated 28 targets and 147 signal pathways, including AKT1, HIF-1α, GSK-3β, TLR4 and NF-κB, those key targets were also verified by molecular docking. The results of GO and KEGG enrichment analysis showed that the targets of QSHT against CHD were largely associated with inflammatory and oxidative stress, and AKT/HIF-1α and TLR4/NF-κB pathways might be key functional pathways. In vivo, QSHT significantly improved cardiac function and attenuated fibrosis and inflammation. Furthermore, QSHT could significantly inhibit the expression of HIF-1α, TLR4, phosphorylation of AKT1, GSK-3β and NF-κB after MI in ApoE−/− mice.Conclusion: Based on network pharmacology, molecular docking and experimental verification, this study demonstrated that QSHT could improve cardiac function and attenuate cardiac fibrosis by regulating TLR4/NF-κB and AKT/HIF-1α signaling pathway in post- MI and high-fat diet ApoE−/− mice.Keywords: network pharmacology, molecular docking, Qushi Huatan decoction, coronary heart disease